Implementation Of The LLM Model For Inventory Management In `UD Murni Bitung Company - Pattinaja, Andreas Timothy; Sondakh, Debby Erce (12th International Scholars Conference 2025, 2026)
In the digital era, efficiency in inventory management is a key factor for the success of commodity distribution companies. UD Murni Bitung, a salt distribution company, still applies a manual stock recording process, which is prone to errors and inefficiencies. This research proposes the development of a mobile-based inventory management system integrated with a Large Language Model (LLM) using Retrieval-Augmented Generation (RAG). The system allows real-time stock monitoring, automated reporting, and interactive chatbot features to assist administrators in making strategic decisions. The prototyping method is applied to iteratively develop the system based on user feedback. The results indicate that the integration of LLM with RAG improves operational accuracy, reduces recording errors, and optimizes decision-making processes in inventory management.